Avaliação e autoavaliação da produção escrita de alunos do 7º ano: avanços, tensões e desafios - Schnorr, Lucilene Aparecida Spielmann (2016)
A student‟s written work is often seen as a ready and finished product, which leads us to seek for “grammatical errors”. Aspects such as content, coherence and compliance of the paper are given less attention than the deviations from the standard form. It is required to emphasize a particular textual component, however we cannot lose sight of the idea that a text comprehends a dialogic project. Such project should be done by the choice of a discourse of genre and materialized through a text. This shows the need to focus on other aspects and to evaluate them in case of difficulties observed in the work of students and propose activities to overcome them. With this understanding, we intend to reflect on the process of evaluation of written texts by the students from the 7th grade of a State Public School in a County in the West region of Parana, in order to verify whether the application of such resources contributes to a better student‟s academic achievement. The classroom was the context of our study, which became the phenomenon in investigation: the evaluation of written textual production. As a teacher-researcher, we are interested in understanding this phenomenon through the investigation of our own pedagogical practice. Thus, the general objective of this research was to analyze the effects of the application of diagnostic tools for evaluation and self-assessment of textual writing production and the use of different forms of textual correction, including the proposed forms by Serafini (1998), Ruiz (2013[2001]) and Biasotto and Conceição (2015). Therefore, the reflection comprised the discussion of criteria, evaluation tools and ways of correction presented to the class through different strategies of interaction between the teacher and students. Located in the field of Applied Linguistics, it is a qualitative-interpretive research, with ethnographic, characterized as action research. The analyzes performed made possible to verify that the objectives of this research were achieved. The use of evaluation and self-assessment tools and different forms of correction of written textual production, allowed the teacher a more accurate recognition of the dominated and nondominated aspects in textual production, by ways of dialogue that led the students, progressively, to a better academic performance.